Visitor and non-visitor destination images : the influence of political instability in South-Eastern Europe - Hughes, Howard L. (Array, 2008)
Summary: Against the lingering legacy of war and political instability, the destination image is one of the most important issues for destination policy makers, as it has a decisive role to play in the destination choice process. The aim of the study reported here was to determine the images of countries of ex-Yugoslavia as tourism destinations. In contrast to image studies that have usually adopted structured (questionnaire) approaches and have mostly identified images of those who had visited a place, in this study qualitative approach was adopted. Data-collection was by way of semi-structured interviews with people who had and with people who had not visited any one of these countries. The research was carried out, on convenience grounds, in Manchester. The interview was structured around the image of these countries in general, atmosphere expected and the listing of distinctive tourism attractions. The issues raised were further refined to ask about "general" image and also image as a holiday destination as well as to determine what factors might inhibit and what factors might facilitate a visit. Both, visitors and non-visitors commonly referred to culture, people and natural attributes of the countries when describing images held. There was a degree of discernment of differences between countries and also of differences in the key area of "security". Images as holiday destinations held by all were positive but especially so for visitors. Non-visitors were generally amenable to the idea of visiting ex-Yugoslavia for a holiday and were aware that the conflict had been more intense in some parts of the region than in others though the image was sometimes applied to all